Study of efficacy and safety of levosalbutamol versus racemic salbutamol delivered by metered dose inhaler in children with moderate persistent asthma - Dr. Sarita Sharma; Dr. Joseph L. Mathew; Dr. Meenu Singh (Pediatric Review: International Journal of Pediatric Research, 2019)
Aim: To compare the efficacy and safety of Levosalbutamol versus racemic Salbutamol delivered by metered dose inhaler in children with moderate persistent asthma.Materials and Methods: Children enrolled in the study were randomized to receive MDI Levosalbutamol 2 puff thrice daily, 50 µgm/puff (group A) or MDI Racemic Salbutamol 2 puff thrice daily. 100 µgm/puff (group B).Baseline characteristics of both groups were comparable. The FEV1 % and PEF % were assessed at baseline, at 15 minutes following the first dose on day 1 and on day 8. In children who remained symptomatic on day 8, an additional evaluation on day 15 was performed. Asthma symptom score were calculated from symptom score card.Results: There was significant improvement in PEF % and FEV1 % within each group. But there was no statistically significant inter-group difference in PEF % change and FEV1 % change except mean change in PEF % and ∆PEF % of initial on day 8 (at the end of 1 week).Asthma symptom score improved significantly in both groups but there was no inter group difference. Incidence of side effects like decrease in serum potassium level and increase in heart rate were comparable in between the two groups.Conclusion: Levosalbutamol administered via MDI improved PEF % significantly more in comparison of racemic Salbutamol after regular use of one week. However, no significant differences were observed in between the two drugs with respect to pulmonary function test on day 1, FEV1 % on day 8 and asthma symptom score. The side effect profile of the two drugs was comparable. This suggests that Levosalbutamol is at least as efficacious as conventional Salbutamol in terms of clinical efficacy.